The Turán Density of the Hypergraph {abc,ade,bde,cde} - Füredi, Zoltán; Pikhurko, Oleg; Simonovits, Miklós (The Electronic Journal of Combinatorics, 2003)
Let F_3,2 denote the 3-graph {abc,ade,bde,cde}. We show that the maximum size of an F_3,2-free 3-graph on n vertices is (49+o(1)) n3, proving a conjecture of Mubayi and Rödl [J. Comb. Th. A, 100 (2002), 135–152].